Isolation and Characterization of Gut Bacterial Proteases Involved in Inducing Pathogenicity of Bacillus thuringiensis Toxin in Cotton Bollworm, Helicoverpa armigera - Regode, Visweshwar; Kuruba, Sreeramulu; Mohammad, Akbar S.; Sharma, Hari C. (Frontiers in Microbiology, 2016)
Bacillus thuringiensis (Bt) toxin proteins are deployed in transgenic plants for pest management. The present studies were aimed at characterization of gut bacterial proteases involved in activation of inactive Cry1Ac protoxin (pro-Cry1Ac) to active toxin in Helicoverpa armigera. Bacterial strains were isolated from H. armigera midgut and screened for their proteolytic activation towards pro-Cry1Ac. Among twelve gut bacterial isolates seven isolates showed proteolytic activity, and proteases from three isolates (IVS1, IVS2 and IVS3) were found to be involved in the proteolytic conversion of pro-Cry1Ac into active toxin. The proteases from IVS1, IVS2 and IVS3 isolates were purified to 11.90-, 15.50- and 17.20-fold, respectively. The optimum pH and temperature for gut bacterial protease activity was 8.0 and 40 oC. Maximum inhibition of total proteolytic activity was exerted by PMSF followed by EDTA. Fluorescence zymography revealed that proteases from IVS1, IVS2, and IVS3 were chymotrypsin-like and showing protease band at ~15, 65 and 15 kDa, respectively. Active Cry1Ac formed from processing pro-Cry1Ac by gut bacterial proteases exhibited toxicity towards H. armigera. The gut bacterial isolates IVS1, IVS2 and IVS3 showed homology with Bacillus thuringiensis (CP003763.1), Vibrio fischeri (CP000020.2) and Escherichia coli (CP011342.1), respectively. Proteases produced by midgut bacteria are involved in proteolytic processing of Bt protoxin and play a major role in inducing pathogenicity of Bt toxins in H. armigera.